Calcium Phosphate-Based Biomaterials for Bone Repair - Xiaodong Hou; Lei Zhang; Zifei Zhou; Xiong Luo; Tianlong Wang; Xinyu Zhao; Bingqiang Lu; Feng Chen; Longpo Zheng (Journal of Functional Biomaterials, 2022)
Traumatic, tumoral, and infectious bone defects are common in clinics, and create a big burden on patient’s families and society. Calcium phosphate (CaP)-based biomaterials have superior properties and have been widely used for bone defect repair, due to their similarities to the inorganic components of human bones. The biological performance of CaPs, as a determining factor for their applications, are dependent on their physicochemical properties. Hydroxyapatite (HAP) as the most thermally stable crystalline phase of CaP is mostly used in the form of ceramics or composites scaffolds with polymers. Nanostructured CaPs with large surface areas are suitable for drug/gene delivery systems. Additionally, CaP scaffolds with hierarchical nano-/microstructures have demonstrated excellent ability in promoting bone regeneration. This review focuses on the relationships and interactions between the physicochemical/biological properties of CaP biomaterials and their species, sizes, and morphologies in bone regeneration, including synthesis strategies, structure control, biological behavior, and the mechanisms of CaP in promoting osteogenesis. This review will be helpful for scientists and engineers to further understand CaP-based biomaterials (CaPs), and be useful in developing new high-performance biomaterials for bone repair.